The impact of Project Management Offices on organizational performance: a comprehensive review of the literature - Syalevi, Rahmad (2024)
In today's dynamic environment, information technology (IT) stands as the cornerstone for organizational success and competitive advantage, with project management playing a crucial role in efficiently deploying IT resources. Recognized across diverse sectors like telecommunications, aerospace, and construction, Project Management Offices (PMOs) facilitate task organization and supervision, whether it is for IT product development, service improvement, system design, or implementing organizational changes. Despite extensive research on the positive impact of PMOs on organizational performance, a significant research gap exists due to the absence of a direct comparison between the influence of PMOs on IT and non-IT industries, indicating the necessity for further investigation in this domain. This study delves into the contribution of PMOs to organizational performance using the Competing Values Framework and evaluates five models and 17 performance metrics within the IT industry and across sectors. When comparing PMO performance, non-IT sectors precede interpersonal relationships, competency-based training, and workplace environment, whereas IT sectors emphasize the knowledge of PMO resource teams, efficient training, technology utilization, and collaboration for project success. Additionally, IT industries underline the role of technology in averting project management failures and prioritizing the punctual delivery of client requirements. These differences highlight the variations in PMO priorities between these industries, underscoring the significance of PMOs in enhancing organizational performance.